CNS Vasculitis Associated with Waldenström Macroglobulinemia - Tanawan Riangwiwat; Chris Y. Wu; Alberto S. Santos-Ocampo; Randal J. Liu; Aaron M. McMurtray; Beau K. Nakamoto (Case Reports in Neurological Medicine)
Waldenström macroglobulinemia (WM) is an indolent B cell lymphoproliferative disorder with monoclonal IgM secretion. We present a patient with WM who presented with multifocal acute cortical ischemic strokes and was found to have central nervous system (CNS) vasculitis. Workup was negative for cryoglobulins and hyperviscosity syndrome. Immunosuppression with intravenous steroids and cyclophosphamide stabilized the patient’s mental status and neurologic deficits. On followup over 7 years, patient gained independence from walking aids and experienced no recurrences of CNS vasculitis. To our knowledge, CNS vasculitis in a WM patient, in the absence of cryoglobulins, has not been reported. Immunosuppression is the preferred treatment.